Integration of Health Education and Character Building in Children through Ecoliteracy Learning: A Multiple Case Study in Early Childhood Education - Tika Pustika Fersari; Amirrudin Muhammad (Lia Center of Research and Education, 2025)
This research examines ecoliteracy-based learning practices that integrate health education and character building in Early Childhood Education settings using a qualitative multiple case study approach. The research uses a qualitative approach with a multiple case study design conducted in three Early Childhood Education institutions in the city of Pangkalpinang, Bangka Belitung Islands Province. Data were collected through participatory observation, in-depth interviews with teachers and parents, as well as document studies, and then analyzed using thematic analysis assisted by NVivo. Research results indicate that ecoliteracy implementation in Early Childhood Education is manifested through three principal patterns: routine-based habituation, narrative-reflective learning and participatory experiential activities. Collectively, these three approaches demonstrate how ecological awareness, clean and healthy lifestyle practices, and holistic character development are meaningfully integrated in children’s daily learning experiences. In addition to increasing environmental awareness, ecoliteracy-based learning also contributes to strengthening values of responsibility, discipline, empathy, and cooperation in young children. The findings position ecoliteracy as an integrative pedagogical approach relevant to sustainability, health, and character education, with implications for educators and policymakers in developing sustainability-oriented early childhood learning.